2019
DOI: 10.1084/jem.20190701
|View full text |Cite
|
Sign up to set email alerts
|

Impact of naturally forming human α/β-tryptase heterotetramers in the pathogenesis of hereditary α-tryptasemia

Abstract: Both α-tryptase and β-tryptase are preferentially expressed by human mast cells, but the purpose of α-tryptase is enigmatic, because its tetramers lack protease activity, whereas β-tryptase tetramers are active proteases. The monogenic disorder called hereditary α-tryptasemia, due to increased α-tryptase gene copies and protein expression, presents with clinical features such as vibratory urticaria and dysautonomia. We show that heterotetramers composed of 2α- and 2β-tryptase protomers (α/β-tryptase) form natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 53 publications
3
110
0
Order By: Relevance
“…Indeed, Lyons et al (2016) reported the contribution of α-tryptase gene copy number to serum α-tryptase levels and the severity of disease phenotype. These earlier findings from Lyons et al (2016) are consistent with the observations from the Le et al (2019) study, which showed that higher α/β-tryptase gene dosage correlates with higher tryptase activity. Moreover, the higher relative stability of α/β-tryptase compared with β-tryptase may account for the enhanced degranulation response observed in the Le et al study.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Indeed, Lyons et al (2016) reported the contribution of α-tryptase gene copy number to serum α-tryptase levels and the severity of disease phenotype. These earlier findings from Lyons et al (2016) are consistent with the observations from the Le et al (2019) study, which showed that higher α/β-tryptase gene dosage correlates with higher tryptase activity. Moreover, the higher relative stability of α/β-tryptase compared with β-tryptase may account for the enhanced degranulation response observed in the Le et al study.…”
supporting
confidence: 90%
“…Vibration was used to trigger mast cell degranulation, as vibratory urticaria was reported to be a common symptom in patients with hereditary α-tryptasemia. Le et al (2019) also revealed the elements of time dependency and dose dependency in the mechanism of action of α/β-tryptase in modulating downstream inflammatory responses. Hence, their findings suggest that patients with relatively higher α-tryptase gene dosage could exhibit heightened mast cell responses and severity of resultant inflammatory/anaphylactic pathogenesis, particularly in tissues with a high abundance of resident mast cells as well as tryptaseresident cell types.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…MCs from these patients do not appear to be more prone to degranulation, indicating the problem is not a disorder of MC activation [29]. A recent study found that in these patients, α-tryptase forms tetramers with β-tryptase in MCs and mediates the biological activity and hence symptoms of hereditary α-tryptasemia [30].…”
Section: Familial Hypertryptasemiamentioning
confidence: 88%